Determination of Benzoate Sodium Level in Some Fruit Juice and Soft Drink Brands in Derna Market by UV- Spectrophotometric Method - AL-Mansouri , Salema; Fatimah AL-Qadeeri (AlQalam Journal of Medical and Applied Sciences, 2025)
In the food and beverage industry, sodium benzoate is widely used due to its antimicrobial effectiveness. This study aimed to determine the concentration levels of sodium benzoate in various 20 commercially available beverages in Derna- Libya using a rapid and simple UV spectrophotometer. The effectiveness of the method appeared to have good accuracy; with a mean recovery of 96.8% to 105% for benzoate, the analyzed samples were classified into two categories: fruit juice and soft drinks. The results showed that sodium benzoate concentrations in juice samples ranged from 1.388–67.44 ppm, while soft drink samples exhibited higher concentrations ranging from 7.995–80.368 ppm. The lowest concentration was recorded in the Sabrina-almond drink (Ajilat- Libya) (1.388 ppm), whereas the highest was found in the frizbi (Turkey) (80.368 ppm). All measured levels were within the acceptable limits established by international standards, including those of the World Health Organization (WHO), confirming that all tested products are safe for human consumption.